2010
DOI: 10.1007/s00775-010-0681-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urea-induced unfolding on the redox process of immobilised cytochrome c

Abstract: We have studied the effect of urea-induced unfolding on the electron transfer process of yeast iso-1-cytochrome c and its mutant K72AK73AK79A adsorbed on electrodes coated by mixed 11-mercapto-1-undecanoic acid/ 11-mercapto-1-undecanol self-assembled monolayers. Electrochemical measurements, complemented by surface enhanced resonance Raman studies, indicate two distinct states of the adsorbed proteins that mainly differ with respect to the ligation pattern of the haem. The native state, in which the haem is ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 76 publications
(114 reference statements)
3
54
0
Order By: Relevance
“…A polycrystalline gold wire was used as a working electrode, a Pt sheet and a saturated calomel electrode as counter and reference electrode, respectively. The working gold electrode was functionalized as reported elsewhere [9]. CV experiments on the protein-coated electrodes were performed using a working solution containing 9 M urea, 10 mM NaClO 4 and 5 mM phosphate buffer at given by the urea-unfolded immobilized ycc and its variants was studied by gradually adding aliquots of a H 2 O 2 solution at known concentration to the above solution under argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A polycrystalline gold wire was used as a working electrode, a Pt sheet and a saturated calomel electrode as counter and reference electrode, respectively. The working gold electrode was functionalized as reported elsewhere [9]. CV experiments on the protein-coated electrodes were performed using a working solution containing 9 M urea, 10 mM NaClO 4 and 5 mM phosphate buffer at given by the urea-unfolded immobilized ycc and its variants was studied by gradually adding aliquots of a H 2 O 2 solution at known concentration to the above solution under argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Although the role of the peroxidase activity of unfolded cytc is well established in several physiological and pathological contexts, the mechanistic details of the process and the structure of the unfolded species remain largely unknown. Previous studies showed the presence of two distinct states of surface-immobilized unfolded cytc differing mainly in the axial ligation of the heme center [9]. In particular, a native-like state is observed under mild unfolding conditions, in which the heme is still axially coordinated by Met80 and His18.…”
Section: Introductionmentioning
confidence: 96%
“…According to the reported, the exposure of heme cofactor to solvent and the nature of the axial ligand seems to be the principal determinant for the magnitude of the formal potential 40,47,48. According to the reported, the exposure of heme cofactor to solvent and the nature of the axial ligand seems to be the principal determinant for the magnitude of the formal potential 40,47,48.…”
mentioning
confidence: 94%
“…Based on the reported results, the magnitude of the formal potential depends mainly on exposure of heme cofactor to solvent, the nature of the axial ligand [45] and the surface charge property of absorbed film [46]. For a partially unfolded cyt c [39,47], its oxidized form always opens the heme crevice due to the change of ligand so as to have a large solvent accessibility of the heme, while its reduced form possesses a relatively compact conformation, which determines the negative shift of its formal potential relative to native cyt c. Since the structure and related heme microenvironment of cyt c treated with SiO2 NPs were changed in the oxidized form while were kept in the reduced form relative to those of native cyt c as shown in Fig.…”
Section: Seiras and Potential-induced Seira Difference Spectroscopy Smentioning
confidence: 99%